Landscape and writing in Los llanos (2020) by Federico Falco (Anclajes, 2024)
This article examines the relationship between landscape and writing in the novel Los llanos by Federico Falco, and reflects on the use of the landscape in the Rio de la Plata context and in the Argentine literary tradition. Following the arguments of Graciela Speranza, Jens Andermann, Graciela Silvestri, Fernando Aliata and Horacio González, it poses questions such as: How does this novel stage the story of the pampa as landscape? In what ways does it develop the idea of ​​the pampa as a remain? Where does Los llanos’s difficult work in trying to describe the plain lead us?
Keywords: Federico Falco; Argentine literature; Landscape; Writing; Argentine literary tradition